EFFECTIVENESS OF DEPLOYING WHATSAPP AND FLASH FICTION IN COMPREHENSION AND LANGUAGE PEDAGOGY - Adekunle Mamudu (University of Kuningan, 2017)
Many universities in Nigeria are yet to embrace technology for pedagogy through the use of modern learning gadgets to enhance learning activities in their campuses. Such modern gadgets include the Global system of Mobile Communication (GSM). In every campus in the country, virtually every student owns a phone and can, thus, participate in at least a two-way communication between the teacher and the learner. Interviews conducted on the poor utilisation of this gadget in schools show that lecturers believe it is highly informal and would, therefore, reduce the seriousness and effectiveness of learning if deployed in and outside the classroom. This study sets out to allay all such fears and convince school administrators that these fears are unfounded. In this research, it was found that rather than weaken the seriousness of learning, it would help the students give their best as they use their regular familiar and endearing phones to respond to their lecturers, while finding the opportunity to quickly consult other language learning-aided packages in their phones. To be specific, this paper examines students’ responses to the use of WhatsApp and flash fiction in the teaching of literary comprehension and appreciation in English Language to learners of English as a second language.Keywords: Flash fiction, WhatsApp, Technology, ICT, English Language Learners